The application of dexamethasone implants in uveitis treatment - Zhang, Tian; Liu, Zhutao; Li, Na (Frontiers in Medicine, 2024)
Uveitis refers to a group of ocular inflammatory diseases that can significantly impair vision. 11 Although systemic corticosteroid therapy has shown substantial efficacy in treating uveitis, extensive12 use of corticosteroids is associated with significant adverse effects. Recently, a biodegradable, 13 sustained-release implant, namely dexamethasone intravitreal implant (Ozurdex), has beenreported14 for treating non-infectious and infectious uveitis. This review aims to summarize the experiences15 with Ozurdex treatment across various forms of uveitis and to assist readers in understandingthe16 appropriate timing and potential side effects of Ozurdex in uveitis treatment, thereby maximizing17 patient benefits in uveitis management.